Loyola Generativity Scale and Generative Behavior Checklist: A Psychometric Study with Spanish LGBT+ Older Adults - Tatiana Casado; Liliana Sousa; Sara Guerra; Pedro Sá Couto; João Paulo Almeida Tavares (Revista de Enfermagem Referência, 2024)
Background: Generativity has been associated with resilience and life satisfaction in older age, including among lesbian, gay, bisexual, and transgender (LGBT+) older adults.